The Implementation of Information Technology-Based Learning during Covid-19 Outbreak at Elementary School - Eko Prasetio; Suyatno Suyatno (Jurnal Inspirasi Pendidikan, 2021)
Information technology-based learning is the solution for school during the COVID-19 outbreak. This study aims to describe the implementation of information technology-based learning in developing cognitive, affective, and psychomotor aspects of the students in SD Muhammadiyah of Krangkajen, Yogyakarta. The research is qualitative research using a study case. The research subjects were a school principal, a vice of the school principal, school treasurer, homeroom teacher, students’ parents, and the students, in which the research subjects were determined by purposive sampling technique. The data were collected through observation, in-depth interviews, and the study of documentation. The research result showed that information technology-based learning in developing cognitive, affective, and psychomotor aspects of the students in SD Muhammadiyah of Karangkajen conducted through the stages; 1) the schools carry out careful planning related to teacher training and infrastructure in supporting learning in COVID-19 outbreak; 2) the implementation of information technology-based learning is diverse and structured innovatively, creatively, and communicatively; 3) the evaluation of information technology-based learning is more emphasized on using digital media appropriate with the certain grade level in order to achieve the expected competencies. Information technology-based learning in SD Muhammadiyah of Karangkajen is be able to lead students to improve learning outcomes in both cognitive, affective, and psychomotor aspects.